Measurement of Current Signature in Three-Phase Induction Motor to Detection of Bearing Failure - Shafie, Aiman Fikrie; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2023)
Three-phase induction motor is the type of motor that is commonly used in many industries. Due to this heavily used type of motor in the industry, the probability of this machine experiencing bearing failure is high. The main aim of this study is to compare the current signature of the three-phase induction motor during normal condition and during bearing failure with varying the torque from 0%, 20%, 40%, 60%, 80%, and 100%. The material used to perform this study was a three-phase induction motor, current clamp, oscilloscope, normal and faulty bearings (outer, inner, and cage failures). As for the method, motor current signature analysis (MCSA) was used to detect the current signature since each failure has its own unique signature. The current clamp was clamped at one of the phases (R-Y-B) and connected to the oscilloscope to perform the MCSA. After conducting the study, the amplitude ( up to 10 kHz high-frequency domain increased when the torque was varied from 0% to 100% for normal conditions, while the amplitude value ( shows increment and decrement for outer, inner and cage failures at both drive end and non-drive ends. In conclusion, the study successfully used MCSA to differentiate the amplitude value for normal and bearing failure conditions for 0% until 100% torque but it was difficult to detect the changes in sideband frequency for bearing failure conditions. Last but not least, using a high-resolution of data acquisition system was suggested to obtain more accurate results.